Metode Pembelajaran Bahasa Arab - Nur Rokhhmatulloh (Universitas Yudharta Pasuruan, 2017)
Learning plays an important role in maintaining the lives of a group of human beings (nations) in the midst of increasingly fierce competition among other nations that advance ahead of learning. From here learning is a process so that humans can make life more alive that has a better direction and can be useful for other humans, so that human life can survive as humans who are educated, moral and civilized. But many are found in the learning process that occurs without regard to the psychological and sociological conditions of students which will actually have a negative impact and will result in mental and soul disturbed and damage the social order. This shows that "learning" or "knowing language" does not always, even often, do not involve "teaching". What must exist in a state of language learning like this is (1) the need to learn / obtain a communication system (language), and (2) there are examples or "models" of communication. Therefore, in a language learning there must be a communicative learning method that can shape abilities both internally and externally, which not only improve in terms of cognitive but also in terms of affective, psychomotor and can affect the environment with positive values and constructive so that the results of the learning process can be perfect and reliable.